A new hysteresis model based on force–displacement characteristics of magnetorheological fluid actuators subjected to squeeze mode operation. (16th May 2017) - Chen, Peng; Bai, Xian-Xu; Qian, Li-Jun; Choi, Seung-Bok
Abstract: This paper presents a new hysteresis model based on the force–displacement characteristics of magnetorheological (MR) fluid actuators (or devices) subjected to squeeze mode operation. The idea of the proposed model is originated from experimental observation of the field-dependent hysteretic behavior of MR fluids, which shows that from a view of rate-independence of hysteresis, a gap width-dependent hysteresis is occurred in the force–displacement relationship instead of the typical relationship of the force–velocity. To effectively and accurately portray the hysteresis behavior, the gap width-dependent hysteresis elements, the nonlinear viscous effect and the inertial effect are considered for the formulation of the hysteresis model. Then, a model-based feedforward force tracking control scheme is established through an observer which can estimate the virtual displacement. The effectiveness of the proposed hysteresis model is validated through the identification and prediction of the damping force of MR fluids in the squeeze mode. In addition, it is shown that superior force tracking performance of the feedforward control associated with the proposed hysteresis mode is evaluated by adopting several tracking trajectories.